Analisis Hubungan Kelimpahan Plankton di Permukaan Terhadap Hasil Tangkapan Ikan Lemuru (Sardinella lemuru) di Selat Bali - Sihombing, Hasanuddin Parulian; Hendrawan, I Gede; Suteja, Yulianto (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.151-161, 2017)
Lemuru fish is one of fishery commodity that has high economical value and one of fish that most catched by fisherman in Bali Strait. Lemuru fish had been caught in Bali Strait was fluctuating every month and every years. This condition was related with food source of Lemuru fish such as phytoplankton and zooplankton. So this research was conducted to explained the relationship phytoplankton and zooplankton abundance with Lemuru fish catched  in Bali strait. This study focus in Bali strait during March until May 2017. Determination of sampling point used area sampling method while water sampling occured in surface water with pouring method. Total of phytoplankton and zooplankton abundance in Bali strait in March until May had formed the sinusoidal model with their abundance ranged 301 ind/L – 604 ind/L and 7 ind/L – 12 ind/L. Plankton abundance in Bali strait in March until May (transisonal season 1) was categorized low abundance if compared with plankton abundance in another season. The low value of phytoplankton abundance caused by non upwelling phenomenon and grazing process and the low abundance of zooplankton caused by low rate of zooplankton and predation by Lemuru fish. Phytoplankton and zooplankton abundance had  strong relationship with Lemuru fish catched with correlation coefficient value 0.76 and 0.69. This condition caused by phytoplankton and zooplankton are source of Lemuru fish food.